Meddelelser om Kvægudførslen til Storbritanien. Foredrag, d. 12te Decbr. 1866. - Mestring, G. (Tidsskrift for Landøkonomi, 2018)
Meddelelser om Kvægudførslen til Storbritanien. Foredrag, d. 12te Decbr. 1866.